An Evidence-Driven Approach to Slip and Fall Prevention in Large Campus Facilities - Michael Yit Lin Chew; Ashan Senel Asmone; Mark Tiam Weng Lam (Buildings)
We developed an evidence-based risk assessment and benchmarking framework towards pedestrian safety. Pendulum slip resistance tests were conducted on 23 sites within a large campus facility covering ceramic tiles, pebbles, tactile indicators, and metal coverings for manholes and drainage. The results show frictional resistance can be reduced when tested wet and exacerbated when it is on a slope. The results were further verified via laboratory tests under controlled conditions. The perceived affordance of certain features such as tactile indicators providing a better grip or traction requires urgent attention. Therefore, a data-driven approach not only enhances the accuracy of slip risk assessments but also establishes empirically grounded benchmarks for surface safety, ensuring effective and resource-efficient interventions. The findings contribute to the existing body of knowledge and future research agenda in pedestrian safety, offering a robust foundation for benchmarking and risk management efforts in diverse environments.